A atuação do IPAAM na gestão ambiental e aplicação da lei delegada n.º 102, de 18 de maio de 2.007, de acordo com os aspectos técnicos que determinam o princípio da precaução e eficiência com análise da eficácia e da efetividade do IPAAM - Lima, Adriana Almeida (2016)
The principles of precaution, efficiency and effectiveness are important optimization commandments for environmental management IPAAM, especially in the implementation of environmental legislation in the state of Amazonas. . In this sense, the objective of this research is to describe the main technical aspects - professional and institutional determining the effectiveness, efficiency and effectiveness of environmental management in IPAAM in the state of Amazonas, Brazil, for this is operationalized the following specific objectives: a) Describe the main features of principles: Precaution, the effectiveness, efficiency and effectiveness in environmental law and its relationship to environmental administrative management; b)Describe on environmental management and environmental management in IPAAM; c) Identify key aspects of the inspection made by the Court of the state and d) Relate the principles: Precaution, the effectiveness, efficiency and effectiveness in Environmental Law in environmental administrative management IPAAM. The methodology is divided into two characterizations: I. types of research, consisting of monographic studies and case study; II. approach methods and procedure, you select the critical-dialectical, by allowing the systemic analysis of environmental management IPAAM and II. research techniques, as follows: direct documentation, have field research, particularly through interviews; indirect documentation, the use of documents and bibliographies on the subject, in particular legislation and scientific references; direct observation, intensive because it is field research, using interviews and extensive, the use of questionnaires and interviews with semi-structured questionnaires. In order to make a survey of the application forms and questionnaires in the amount of seventy (70) respondents. Finally, by applying the questions were made 10 (ten) interviews, was originated the data of descriptive statistics.